Barriers to sexual health care: a survey of Iranian-American physicians in California, USA. Issue 1 (December 2016) - Rashidian, Mitra; Minichiello, Victor; Knutsen, Synnove; Ghamsary, Mark
Abstract Background Despite increasing numbers of Iranian-American physicians practicing in the United States, little is known about the barriers that may impact them as providers of sexual health care. This is an important topic as discussions of sexual topics are generally considered a taboo among Iranians. We aimed to identify barriers experienced by Iranian-American physicians that inhibit their willingness to engage in discussions of sexual health care with patients. Methods In 2013, a self-administrated questionnaire was sent to 1, 550 Iranian-American physicians in California. Questions included demographics of the physicians as well as their perception of challenges in discussing various sexual health topics with their patients. Factor analysis: Principal components approach with a Varimax rotation was used to detect latent factors within the data that may help explain possible barriers to discussion of sexual health among physicians. The analysis was performed on 11 items, specifically focused on possible barriers, to detect a possible relationship between correlated variables within the data to produce a set of uncorrelated variables (factors). Results The overall response rate was 23 %. Data revealed specific barriers regarding sexual history taking, discussing STIs and sexual dysfunctions with patients based on their gender, and age. Three factors were identified as internally consistent (Cronbach's alpha = 0.82 to 0.91): (i) embarrassment, (ii) cultural and religious, (iii) lack of time and financial constraint. Significant associations were found between these 3 factors and some variables such as: country of medical graduation, religious affiliation, birthplace, age, and gender. Conclusions Our findings are the first to identify possible barriers among Iranian-American physicians in delivering effective sexual health care to patients. Additional studies from Iranian-American physicians as well as from other foreign-born/subpopulation of US physicians populations and mainstream US physicians are needed to assess the extent of such barriers, and changes over time. Effective strategies to better engage such physicians in these studies are needed. If confirmed from other studies, our findings could have implications for the training of US medical graduates.